2004
DOI: 10.1128/jvi.78.17.9270-9276.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Glycan-Controlled Epitopes of Prion Protein Include a Major Determinant of Susceptibility to Sheep Scrapie

Abstract: A key feature of prion encephalopathies is the accumulation of a misfolded form of the host glycoprotein PrP. Cell-free and cell culture studies have shown that the efficiency of conversion of PrP into the disease-associated form is influenced by its amino acid sequence and also by its carbohydrate moiety. Here, we characterize four novel glycoform-dependent monoclonal antibodies raised against prokaryotic recombinant sheep PrP. We demonstrate that these antibodies discriminate the PrP monoglycosylated species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 50 publications
(63 reference statements)
5
35
2
Order By: Relevance
“…1). The mobility of the glycosylated species appeared overall to be slightly lower for site 1 than that for site 2 mutants, consistent with the lower molecular mass of the glycan chain attached to site 1 (37). Additional site 1 glycosylation mutants were produced by replacing T (instead of N) in the consensus sequon by either A or N, the glycoform pattern of which did not differ from that of N184X mutants (data not shown).…”
Section: Resultsmentioning
confidence: 71%
“…1). The mobility of the glycosylated species appeared overall to be slightly lower for site 1 than that for site 2 mutants, consistent with the lower molecular mass of the glycan chain attached to site 1 (37). Additional site 1 glycosylation mutants were produced by replacing T (instead of N) in the consensus sequon by either A or N, the glycoform pattern of which did not differ from that of N184X mutants (data not shown).…”
Section: Resultsmentioning
confidence: 71%
“…Instead, the preferential binding of PRC7 to under-glycosylated PrP suggests that occupancy of one of the two PrP N-linked glycosylation sites precludes antibody binding to the fully glycosylated protein, making it immunologically silent to PRC7. A similar mechanism has been suggested to explain the properties of previously isolated glycosylation-dependent antibodies (13,19,47).…”
Section: Prc Mabs Discriminate Prp Polymorphisms and Prpmentioning
confidence: 84%
“…Susceptibility of sheep to classical scrapie is strongly associated with amino acid polymorphism at this residue, as well as polymorphisms at residues 154 and 171 (46). Although previous studies have shown mAbs to be capable of distinguishing OvPrP-Q171 and OvPrP-R171 allotypes (47,48), the direct involvement of residue 171 in these epitopes was not demonstrated, and in the case of glycosylation-dependent antibodies, the effect was indirectly influenced by N-linked glycan occupancy of OvPrP (47). Recognition by PRC1 is also dependent on a known PrP polymorphism.…”
Section: Prc Mabs Discriminate Prp Polymorphisms and Prpmentioning
confidence: 95%
“…In PrP-ins(His 6 ) and PrP-ins-(FLAG), in particular, the calculated isoelectric point and charge at pH 7 of the loop segment were markedly modified. PrP C and PrP Sc Conformations of Insertion Mutants in Position 203-The loss of the conformational V14 epitope in PrPins203 might suggest some local dynamic change of the conformation of the region immediately upstream of the insert (56), as the epitope was reported to cover the domain between the two glycosylation sites, from the middle of H2 to the beginning of the H2-H3 loop (5,41). However, another possibility is that the size of the segment encompassing the epitope would have been previously underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The 4F2 mAb (40) is an IgG2b directed to the octarepeat domain (54 -92, sheep PrP numbering) and was used to detect PrP C ; Sha31 mAb (epitope 148 -159) (40) was used to detect PrP res on immunoblots. The V14 mAb (IgG2a) recognizes a conformational epitope (191)(192)(193)(194)(195)(196)(197)(198)(199), sensitive to the presence of N-glycan chains (5,41). ICSM33 (IgG2b, epitope 91-110, D-Gen Ltd., London) was used to detect denatured PrP Sc by immunofluorescence (42).…”
Section: Methodsmentioning
confidence: 99%